A modified aeolian flux model applicable for various soil particle characteristics - Zou, Xueyong; Shen, Qi; Zhang, Mengcui; Li, Huiru; Kang, Liqiang; Zhang, Chunlai; Cheng, Hong; Wu, Xiaoxu; Li, Jifeng (Catena (Giessen), 2022)
•The characteristic parameters of soil particles (CPSP) were defined.•CPSPs includes the average diameter, sorting coefficient, density and sphericity.•Relationship between aeolian flux and CPSP is non-linear positive correlation.•An aeolian flux model was proposed for soil particle characteristics.•The model can predict aeolian flux of soils with various particles characteristics. The aeolian flux is a key controlling factor for aeolian geomorphic evolution and the spatial redistribution of matter on the surface of the Earth and other planets. Based on theoretical derivation and a series of wind tunnel experiments, a non-linear positive correlation relationship is found between aeolian flux and the average diameter, sorting coefficient, density and sphericity of soil particles. Subsequently, a modified aeolian flux model containing these characteristic parameters of soil particles is proposed. For a wide range of the values of particle characteristic parameters, the prediction ability of the modified model for aeolian flux is satisfactory. These findings substantially deepen the understanding of the influence of soil particle characteristics on aeolian flux, and the modified model significantly improves the ability to predict aeolian flux, which will have an important impact on the aeolian geomorphic evolution, blown-sand disaster prevention and soil wind erosion control in the future.